THE EFFECT OF MACROECONOMIC VARIABLES ON THE YIELD SPREAD OF INDONESIAN GOVERNMENT’S BOND - Utama, Chandra; Agesy, Shela Selviana (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2016)
This study analyzes the roles of macroeconomic variables, which include interest rate (SBI), Consumer Price Index (IHK), Jakarta Composite Index (IHSG), money supply (JUB) and exchange rate (KURS) on yield spread of government bonds (YSI) in Indonesia. The study employs Error Correction Model (ECM) on Indonesian monthly data from January 2008 to December 2013. The study confirms that SBI and KURS significantly determine the YSI in the short run and the long run but money supply is significant only in the long run. However, YSI is not influenced by IHK and IHSG. Based on term structure of interest rate theory, the study finds that the expected future interest rate is determined by SBI, KURS, and JUB.